Practical Issues in Laboratory Information Systems Implementation - Schneider, Charles M. (1982)
Henry Ford Hospital, a 1,049 bed, Detroit area teaching hospital and ambulatory services center, is in the final stages of implementing a vendor-supplied, laboratory computer system. Implementation planning was guided by the desire to minimize disruptions within the hospital system. Efforts focused on obtaining user input into the process of moving from a manual to an automated results reporting system. Operational characteristics as well as mechanisms for eliciting this user response while maintaining realistic expectations for system capabilities are discussed. Special emphasis is given to order entry concerns, result reports and error resolution.